Understanding hydrogen plasma processes based on the diagnostic results of 2.45 GHz ECRIS at Peking University - 武文斌 任海涛 彭士香 徐源 温佳美 孙江 张艾霖 张滔 张景丰 陈佳洱 (Chinese physics B, 2017)
Optical emission spectroscopy（OES）, as a simple in situ method without disturbing the plasma, has been performed for the plasma diagnosis of a 2.45 GHz permanent magnet electron cyclotron resonance（PMECR） ion source at Peking University（PKU）. A spectrum measurement platform has been set up with the quartz-chamber electron cyclotron resonance（ECR） ion source [Patent Number： ZL 201110026605.4] and experiments were carried out recently. The electron temperature and electron density inside the ECR plasma chamber have been measured with the method of line intensity ratio of noble gas. Hydrogen plasma processes inside the discharge chamber are discussed based on the diagnostic results. What is more, the superiority of the method of line intensity ratio of noble gas is indicated with a comparison to line intensity ratio of hydrogen. Details will be presented in this paper.